IMPROVING STUDENTS’ LEARNING OUTCOMES THROUGH THE USE OF SUBSTITUTION DRILLS METHOD IN SIMPLE PRESENT TENSE MATERIAL THE 10TH GRADE OF SOCIAL SCIENCE MAN 1 BANJARMASIN ACADEMIC YEAR 2018/2019 - Fakhrunisa, Fakhrunisa (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari, 2019)
The research about the use of substitute drills learning methods on simple present tense has been carried out which aims to know (1) the increasing activities in implementation classroom action, (2) the increasing student learning outcomes and (3) the student responses in the learning activity by using the substitutions drills strategy. The research conducted a classroom action research design (CAR) with two cycles. Each cycle consists of planning, implementing actions, observing and evaluating, and analyzing and reflecting. The research subjects were the 34 students of 10th grade of social science. Data were collected through observation techniques, learning achievement tests, and questionnaire distribution. Data were analyzed with quantitative descriptive analysis techniques and qualitative analysis. Based on the results of research, by using learning substitutions drills method on simple present tense material can increase the activities of implementing classroom actions and student learning outcomes.